Prevalence and factors associated with teenage pregnancy among pregnant mothers attending Rakai general hospital, Uganda: A cross-sectional study. - Tukirinawe, Happy; Francis, Associate Professor Kazibwe; Nabimanya, Edward; Arinaitwe , Elizabeth; Jean, Rukamba de Dieu; Musinguzi, Ronard; Nakidde, Dr. Gladys; Nowomuhangi, Bonny (Student's Journal of Health Research Africa, 2025)
Background: The World Health Organization defines a teenage pregnancy as a pregnancy below the age of 20 years, and it is a major public health concern affecting more than 16 million girls and young women around the world. This study aimed at determining the Prevalence and Factors associated with Teenage Pregnancy among Mothers attending the Antenatal Care Clinic at Rakai General Hospital. Methods: It was a cross-sectional study where we included pregnant women attending ANC. Using a consecutive sampling method, 251 pregnant women were enrolled. Data was collected using structured pre-tested questionnaires and analyzed using STATA Version 15.1. A bivariate and multivariate analysis was used to show the association between the dependent and independent variables, considering P < 0.05 as the level of significance and the 95% confidence interval. Results: The prevalence of Teenage Pregnancy was 55(21.91%). Mothers with no formal education were 5.8. times more likely to have teenage pregnancy with (aOR =5.8.0; 95% CI = [1.759-19.675]; P=0.004), girls in Peer groups were 3.1 times more likely to have pregnancy in their teenage age with (aOR =3.1; 95% CI = [1.946-12.633]; P=0.016), history of contraception use and age of marriage less than 18 years were also significantly associated with Teenage pregnancy amongst mothers attending Rakai General Hospital Antenatal Care Clinic with, (aOR =3.2; 95% CI = [1.731-13.326]; P=0.001); (aOR =3.9; 95% CI = [1.693-10.075]; P=0.013) respectively. Conclusion: The overall prevalence of Teenage pregnancy is high compared to the global prevalence. Teenage Pregnancy was significantly associated with no formal education, peer groups, a history of contraception use, and an age of marriage of less than 18 years. Recommendations: Conduct a national study on the prevalence, strengthen laws against early marriage, keep girls in school, and sensitize them on teenage pregnancy risks.